DESIGN AND APPLICATION OF RAW MATERIAL INVENTORY FORECASTING METHOD IN RESTAURANT PENYETAN COK. - Husain, Diah Novita; Soebijono, Tony; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Boga Putra Sakti is a company engaged in culinary has several restaurants that Suteki Sushi, penyetan Cok, and Waroeng Sapiku. After successfully opening a restaurant Suteki Sushi, PT Putra Boga Way opened penyetan Cok. The name comes from a word that characterizes the community of East Java, especially Surabaya and surrounding areas, but do not open the choke penyetan outlet firstin Surabaya, but penyetan was first open in Jakarta since 2013. One branch penyetan Cok located in BG Junction has business processes for supply of raw materials. Choke penyetan office to give orders raw materials 2 times a week. The process especially when raw materials side dish usingthought supervisor that making raw material excess or shortage in supply.To overcome these problems, we need a solution that is creating and designing applications on the supply of raw materials choke penyetan restaurant located in BG Junction Surabaya by using the process of the prediction method Exponential Smoothing Wintersresearch produces raw material inventory application using exponential smoothing forecasting method winter on penyetan choke for the upcoming period based on the data demand in the previous period so that it can help the problems of shortage and excess inventory of raw materials, especially dishes.